The use of nanomodified polypropylene mesh with an antiseptic in patients with inguinal hernias during Lichtenstein surgery - Ruslan Lutkovskyi (Kazimierz Wielki University, 2022)
Aloplasty of inguinal hernias (IH), of using modified polypropylene mesh antiseptic and an by carbon nanotubes, buth this is accompanied by a fairly high freguency of postoperative complications from the postoperative wound. In our view, the use of a nanomodified polypropylene mesh modified by carbon nanotubes and an antiseptic of polyhexamethleneguanidme chloride the results of surgical treatment of IH. Aim - to improve the results of surgical treatment of inguinal hernias modified polypropylene mesh antiseptic and an by carbon nanotubes. Materials and methods. The analysis of surgical treatment of 144 patients with IH of has been performed. Depending on the type of mesh used during surgical treatment, patients were divided into 2 groups. In 72 (50%) of Group I patients, using modified polypropylene mesh antiseptic and an by carbon nanotubes. In the 2ndgroup, 72 (50%) patients using classic polypropylene mesh. Results and discussion. Statistically significant results were obtained in patients of Group I compared to Group II: seroma was in 4 (5.6±1.2%) in Group II compared to 2 (2.8±0.4%) in Group I (p<0.05), respectively, the suppuration of the postoperative wound - 4 (5.6±0.4%) to 1 (1.4±0.6%) (p<0.05). The terms of stay of patients of group II on inpatient treatment - 11,2±2,2 days group II - 7,3±1,3 days. Long-term results: ligature fistulas of the anterior abdominal wall were detected in 3 (5.4±0.4%) patients of group II, in patients of group I of the ligature fistulas were not detected (p<0.05), meshoma - in 1 (1.8±0.3%) of patients in group II, in group I there was no stir (p>0.05). Chronic pain in the abdominal wall in 6 - 8 months after surgery was observed in 3 (5.4±0.4)% patients in group II and in 1 (1.8±0.5%) group I (p>0.05), recurrences of hernia were found in 3 (5.4±0.4%) patients of group II, in group I - in 1 (1.8±0.3)% (p<0.05). Conclusion. Surgical treatment of IH using modified polypropylene mesh antiseptic and an by carbon nanotubes the use of the classical polypropylene mesh, namely, reducing the freguency of seroma from 5.6±1.2% in the II group of patients to 2.8±0.4% in group I, respectively, suppurations of postoperative wounds - from 5.6±0.4% to 1.4±0.6%, inflammatory infiltrates - from 5.6±0.4% to 1.4±0.6%, ligaturial fistulas of the anterior abdominal wall - from 5.4±0.4% to 0%, meshoma - from 1.8±0.3% to 0%, chronic postoperative pain - from 5.4±0.4% to 1.8±0.5%, recurrence of hernia-from 5.4±0.4% to 1.8±0.3%.